2016
DOI: 10.1016/j.clinimag.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Imaging comparison of tubular and colloid pancreatic adenocarcinoma arising from intraductal papillary mucinous neoplasm on multidetector CT

Abstract: Purpose To compare tubular and colloid subtype pancreatic ductal adenocarcinomas (PDAC) associated with intraductal papillary mucinous neoplasms (IPMN) on CT. Methods An IRB approved retrospective study included patients with either IPMN tPDAC or cPDAC. Enhancing mural nodules (MN), solid component (SC), main pancreatic duct diameter (MPD), abrupt change in MPD caliber were evaluated. Results 22 patients with cPDAC, 17 with tPDAC showed no significant difference in MPD size. MN and SC were seen in cPDAC/tP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Various types of comprehensive therapies are available and target therapies have been regarded as the most important component of treatments for patients with IPMN; however, the 5-year survival rate of patients with IPMN is still poor ( 5 , 6 ). Notably, although a previous report has indicated that the imaging comparison of tubular and colloid pancreatic adenocarcinoma arising from IPMN on multidetector may be detected by computed tomography (CT) ( 7 ), diagnostic accuracy and sensitivity has not been improved for patients with early-stage IPMN. Furthermore, IPMN is associated with a spectrum of histologic and imaging findings, which have demonstrated the malignant transformation from adenoma to invasive carcinoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various types of comprehensive therapies are available and target therapies have been regarded as the most important component of treatments for patients with IPMN; however, the 5-year survival rate of patients with IPMN is still poor ( 5 , 6 ). Notably, although a previous report has indicated that the imaging comparison of tubular and colloid pancreatic adenocarcinoma arising from IPMN on multidetector may be detected by computed tomography (CT) ( 7 ), diagnostic accuracy and sensitivity has not been improved for patients with early-stage IPMN. Furthermore, IPMN is associated with a spectrum of histologic and imaging findings, which have demonstrated the malignant transformation from adenoma to invasive carcinoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, only small cases studies of CC of the pancreas on MRI and contrast-enhanced CT have been reported ( 6 12 ). However, due to the absence of the typical features on MRI and contrast-enhanced CT, it is always hard to distinguish CC from other pancreatic tumors, such as IPMN and MCN.…”
Section: Introductionmentioning
confidence: 99%